Time to First-Line Antiretroviral Treatment Failure and Its Predictors among HIV-Positive Children in Shashemene Town Health Facilities, Oromia Region, Ethiopia, 2019 - Endale Zenebe; Assefa Washo; Abreham Addis Gesese (The Scientific World Journal)
With expanding pediatric antiretroviral therapy access, children will begin to experience treatment failure and require second-line therapy. In resource-limited settings, treatment failure is often diagnosed based on the clinical or immunological criteria which occur way after the occurrence of virological failure. Previous limited studies have evaluated immunological and clinical failure without considering virological failure in Ethiopia. The aim of this study was to investigate time to first-line antiretroviral treatment failure and its predictors in Shashamene town health facilities with a focus on virological criteria. Methods. A retrospective cohort study was conducted in three health facilities of Shashamene town, Oromia Regional State, from March 1 to 26, 2019. Children aged less than 15 years living with HIV/AIDS that were enrolled on ART between January 1, 2011, and December 30, 2015, in Shashamene town health facilities were the study population. Data were extracted using a checklist, entered into EpiData version 3.1, and exported to SPSS version 20 for data analysis. Cox proportional hazard regression was used to determine the predictors of time to first-line treatment failure. Result. The median survival time to virological failure was 30 months with IQR of 24.42 to 44.25. Baseline WHO stages 3 and 4 with AHR = 5.69 (95% CI: 2.07–15.66) and NVP-based NNRT at initial treatment with AHR = 2.72 (1.13–6.54) were the independent predictors of time to treatment failure. Conclusion. The median survival time of first-line antiretroviral treatment failure was moderate in the study area as compared to other studies. The incidence density of treatment failure in this study was low as compared to other studies. The finding also demonstrated that children treated with nevirapine-based nonnucleoside reverse transcriptase inhibitors at initial and advanced WHO clinical stages at baseline were at higher risk of treatment failure.